The Existence of Autopsy in Assisting The Disclosure of Homicide Crimes - Heldiora Silva Simamora; Janpatar Simamora; Meli Hertati Gultom (International Journal of Law and Society, 2025)
Murder is an inhumane criminal act and can be considered a heinous act, as it takes another person's life, whether done instantly or with prior planning. In the investigation process of a murder case, a specific procedure is required to uncover the incident, namely an autopsy. An autopsy is the examination of a deceased body, deemed to have died unnaturally, by performing surgical procedures to determine the cause of death, estimate the time of death, identify unidentified bodies, uncover the perpetrator, and more. The findings from the autopsy are compiled into a written report prepared by a forensic doctor, known as visum et repertum. Before drafting the visum et repertum, the forensic doctor takes an oath to ensure that the contents of the report can be held accountable. This report will later be used in court as evidence to support other evidence related to the murder.